2022
DOI: 10.1038/s41598-021-03985-3
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient removal of thallium(I) by facilely fabricated amorphous titanium dioxide from water and wastewater

Abstract: In this study, amorphous hydrous titanium dioxide was synthesized by a facile precipitation method at room temperature, aiming to effectively remove thallium(I) from water. The titanium dioxide prepared using ammonia as precipitant (TiO2I) is more effective for thallium(I) uptake than the one synthesized with sodium hydroxide (TiO2II). The TiO2 obtained particles are amorphous, aggregates of many nanoparticles and irregular in shape. The thallium(I) uptake increases with the rise of solution pH value. Under ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Its acute toxicity to humans brings about vomiting, diarrhea, temporary loss of hair; affects the nervous system, lungs, heart, liver, and kidneys; and can even lead to death [9]. Epidemiological data showed that exposure to Tl during pregnancy may also have negative effects on birth outcomes, such as fetal death, congenital malformations, or decreased birth weight [10,11]. An exposure to Tl concentration levels in the range of 0.1 to 100 µg/L may be considered chronic [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its acute toxicity to humans brings about vomiting, diarrhea, temporary loss of hair; affects the nervous system, lungs, heart, liver, and kidneys; and can even lead to death [9]. Epidemiological data showed that exposure to Tl during pregnancy may also have negative effects on birth outcomes, such as fetal death, congenital malformations, or decreased birth weight [10,11]. An exposure to Tl concentration levels in the range of 0.1 to 100 µg/L may be considered chronic [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…To date, few studies have reported adsorption behavior and removal efficiency of thallium (I) at low concentration. As a matter of fact, most of the investigations were carried out at high thallium (I) concentration ranging from 1-150 mg.L −1 , whereas thallium is found to be in the range of a few µg.L −1 in real polluted water sources [11,16,28]. In this paper, the removal of Tl(I) ions at low concentration, through adsorption onto synthesized gamma-alumina nanoparticles, was investigated for the first time.…”
Section: Introductionmentioning
confidence: 99%